A method for objective evaluation of the sensation of the localisation direction of a sound source - MAKOWSKI, Ryszard (Archives of Acoustics, 1984)
This paper proposes a new method allowing the evaluation of the sensation of the localisation direction of an image sound source, generated by signals transmitted by a two - channel loudspeaker stereo - system. This evaluation can be carried out on the basis of the localisation parameters of signals reaching the membrane of the listener’s ear drum, i.e. it does not require psycho-acoustic investigations. The method proposed takes into account the properties of the human hearing organ, as known from psychoacoustic investigations, which are essential in localisation. In the final part of the paper, by using the method proposed, a critical evaluation is carried out of a two - channel loudspeaker intensity stereo - system.